2011
DOI: 10.1042/bj20111199
|View full text |Cite
|
Sign up to set email alerts
|

Directed evolution of a temperature-, peroxide- and alkaline pH-tolerant versatile peroxidase

Abstract: The VPs (versatile peroxidases) secreted by white-rot fungi are involved in the natural decay of lignin. In the present study, a fusion gene containing the VP from Pleurotus eryngii was subjected to six rounds of directed evolution, achieving a level of secretion in Saccharomyces cerevisiae (21 mg/l) as yet unseen for any ligninolytic peroxidase. The evolved variant for expression harboured four mutations and increased its total VP activity 129-fold. The signal leader processing by the STE13 protease at the Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 56 publications
7
115
0
3
Order By: Relevance
“…1A, Southern probe; Table 1, primers). Distinctive patterns of bands for either BglII, EcoNI, or StyI, of 7,195,8,118, or 2,537 and 4,146, 2,227, or 3,059 bp were produced from the wild-type PC9 strain and the ⌬ku80 strains, respectively. This analysis confirmed that ku80 replacement was the result of a single integration event in all three transformants (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A, Southern probe; Table 1, primers). Distinctive patterns of bands for either BglII, EcoNI, or StyI, of 7,195,8,118, or 2,537 and 4,146, 2,227, or 3,059 bp were produced from the wild-type PC9 strain and the ⌬ku80 strains, respectively. This analysis confirmed that ku80 replacement was the result of a single integration event in all three transformants (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…VP is an enzyme with dual activity and wide substrate specificity associated with its high redox potential (E 0 Ͼ ϩ1.4 V), the presence of two catalytic sites, one for the oxidation of low-and high-redox-potential compounds and the second for Mn 2ϩ -oxidizing peroxidase (EC 1.11.1.6) activity. Recent literature points out VP's catalytic promiscuity, which is attracting great interest due to its potential biotechnological applications (7,30). To investigate VP's significance in vivo, it was selected for complete and specific inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…MnP, LiP and VP have been expressed in various Pichia and Saccharomyces strains, the recombinant enzymes were secreted into the medium (e.g. 100 mg L ¡1 and 21.6 mg L ¡1 for Pichia methanolica and Saccharomyces cerevisiae, respectively) 34,35 and catalytic activities were determined using common substrates such as 2,2'azinobis(3-ethylbenzothiazoline-6-sulfonate) (ABTS) and veratryl alcohol (VA). [34][35][36][37][38] MnP produced in this manner was suitable for the treatment of Kraft lignin as determined by measuring the kappa number and the increase in Klason lignin residue.…”
Section: Recombinant Lignin-degrading Peroxidasesmentioning
confidence: 99%
“…100 mg L ¡1 and 21.6 mg L ¡1 for Pichia methanolica and Saccharomyces cerevisiae, respectively) 34,35 and catalytic activities were determined using common substrates such as 2,2'azinobis(3-ethylbenzothiazoline-6-sulfonate) (ABTS) and veratryl alcohol (VA). [34][35][36][37][38] MnP produced in this manner was suitable for the treatment of Kraft lignin as determined by measuring the kappa number and the increase in Klason lignin residue. 39 MnP from P. chrysosporium has also been expressed in the filamentous fungi Aspergillus oryzae and A. niger, 40,41 yielding up to 100 mg L ¡1 in A.…”
Section: Recombinant Lignin-degrading Peroxidasesmentioning
confidence: 99%
“…In the present study, the native signal peptide of AAO was replaced by two different signal sequences to drive its functional expression in Saccharomyces cerevisiae: (i) the signal prepro-leader of the mating ␣-factor of S. cerevisiae, which has been used widely to evolve different ligninases (18)(19)(20)(21)(22)(23), and (ii) the signal prepro(␦)-leader and the ␥-spacer segment of the K 1 killer toxin, which have been seen to be useful in boosting ␤-lactamase secretion in yeast (24,25). For the first time, chimeric versions of these leaders were designed by combining the different pre-and pro-regions, and these constructs were subjected to conventional and focused-directed evolution using a very sensitive dual highthroughput screening (HTS) assay based on the Fenton reaction.…”
mentioning
confidence: 99%